Hubungan Usia Ibu Hamil dengan Kejadian Berat Badan Lahir Rendah di Kecamatan Babakan Madang, Kabupaten Bogor - Fitratur Rahmah Agustina; Sudiarti, Trini; Rusydi, Riska (Media Gizi Ilmiah Indonesia, 2023)
Low Birth Weight (LBW) has serious consequences and is one of the causes of infant death. The incidence of low birth weight in Bogor Regency in 2018 was 1,633 infants (1.38%). This study aims to determine the relationship between maternal age during pregnancy and the incidence of low birth weight in Babakan Madang District, Bogor Regency in 2019. The research design was cross sectional. This study used secondary data obtained from the 2019 PITTA B umbrella research. The population of this study is all children covered in the 2019 PITTA B GRANT data, which is 612 children under five. The number of samples in this study was determined based on inclusion and exclusion criteria so that the selected subjects were in accordance with research needs (eligible subjects), which were 504 children. The results showed that 5.8% of children are low birth weight in Babakan Madang District in 2019. Twenty nine children who experienced low birth weight, 10.6% were born to mothers aged >35 years and 5.3% to mothers aged ≤35 years. The results of chi-square analysis showed that there was no significant relationship between maternal age during pregnancy and the incidence of low birth weight (p = 0.175). The researchers suggest to the Bogor District Health Office to provide socialization and education to the public about the causes and effects of low birth weight, the importance of maintaining maternal health during pregnancy, and other factors that can cause low birth weight.